1985
DOI: 10.1111/j.1600-0897.1985.tb00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐Induced Inhibition of Autoimmune Response to Rat Male Accessory Glands

Abstract: Pretreatment of rats with low doses of purified fraction of rat male accessory glands (containing the autoantigen) markedly reduced the immune response to autoantigen when animals were subsequently challenged with modified rat male accessory glands in complete Freund's adjuvant. The rats pretreated with low doses of antigen prior to immunization showed marked suppression of delayed-type hypersensitivity reaction (P less than 0.001) when compared to control animals (pretreated with rat lung saline extract or 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…in the soluble form before the immunization with MRAG-CFA [7]. The unresponsiveness is specific for the autoantigen at both the cellular and humoral level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the soluble form before the immunization with MRAG-CFA [7]. The unresponsiveness is specific for the autoantigen at both the cellular and humoral level.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports [2- In previous studies we have developed an experimental model of suppression of autoimmune response to chemically modified rat male accessory gland saline extract (MRAG) by i.p. administration of low doses of fraction I (Sephadex G-100) FI of RAG prior to the immunization with MRAG in CFA.The unresponsiveness was specific for the autoantigen at both the cellular and humoral levels [7]. The cell types involved in the suppression included MRAGspecific, cyclophosphamide (a)-sensitive, inducer-phase T, cells.…”
Section: Introductionmentioning
confidence: 98%
“…Using another experimental model of autoimmunity against rat male sex accessory glands induced by immunization with a chemically modified accessory gland saline extract (MRAG) in complete Freund's adjuvant (CFA), we have previously shown that a purified fraction of rat male accessory glands intraperitoneally administered in low doses and soluble form prevents the cellular and humoral autoimmune response when animals are subsequently challenged with MRAG in CFA (Ferro et al , 1985(Ferro et al , , 1990Rivero et al, 199 1). Application of a similar experimental model to EAE demonstrated inhibition of the clinical signs of the disease with a concurrent suppression of the proliferative response of mononuclear cells to MBP (Rivero et al, 1995(Rivero et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account that the relationship of the senescent immunosuppressor system to the aging process remains poorly understood, in this present report we analyze the suppressor autoimmune system using an experimental model of suppression of autoimmunity to MRAG developed in our laboratory [6]. In fact, a state of specific tolerance to MRAG was induced when low doses of purified fractions of RAG were injected i.p.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have analyzed the ability to induce suppression to RAG autoantigens and the characteristics of TJnducer peritoneal cells (PC) of old rats using an experimental model of suppression of autoimmunity to RAG [6,7], in which antigen-specific inducer-phase T, cells, effector-phase suppressor cells and I-E+ APC are involved.…”
Section: Introductionmentioning
confidence: 99%